The Effect of Leadership Style and Management Control System on Organizational Performance - Dwi Marlina Wijayanti (Journal of Accounting Inquiry, 2026)
Purpose: This study analyses the influence of leadership style (initiating structure) and management control systems (diagnostic) on company performance. Methodology: This study employs a quantitative approach, using a self-administered survey as the data collection method. The respondents consist of 86 top-level management executives from various organizations across Indonesia, as they are considered to possess sufficient understanding of company performance and the management control systems implemented. Data analysis was conducted using Structural Equation Modelling with Partial Least Squares (SEM-PLS). Findings: The findings of this study indicate that the initiating structure leadership style has a positive contribution to improving company performance. Furthermore, the diagnostic control system is proven to act as a mediating variable (fully) in the relationship between the initiating structure leadership style and company performance  Novelty: This study contributes to the literature by integrating management control systems with leadership style in explaining company performance, which has not previously been examined within the context of management control system practices. It highlights the mediating role of diagnostic control systems in translating initiating structure leadership into improved performance, providing new insights into how formal controls and leadership behavior interact at the top management level.